ANALYSIS OF THE USE OF INDIRECT EVIDENCE IN THE DECISION OF THE COMMISSION FOR THE SUPERVISION OF BUSINESS COMPETITION CASES NUMBER 04/KPPU-I/2016 AND CASES NUMBER 24/KPPU-I/2009 - Ahmad Misbakh Zainul Musthofa (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2020)
The Business Competition Supervisory Commission in its decision regarding Case Number 04 / KPPU-I / 2016 concerning Alleged Violation of Article 5 Paragraph 1 of Law Number 5 the Year 1999 Concerning Prohibition of Monopolistic Practices and Unfair Business Competition in Matic Scooter Type Motorcycle Industry 110-125 CC in Indonesia conducted by PT. Yamaha Indonesia Motor Manufacturing and PT. Astra Honda Motor, KPPU determined that there was a violation of article 5 paragraph 1 by entering into an agreement to influence the price of a 110-125 CC automatic motorbike by using indirect evidence (Indirect Evidence). In addition, Case Number 4 / KPPU-I / 2016 number 12.2.2 letter G describes concerted action which is defined as the result of an act committed by YIMM and AHM, while the communication behavior carried out by cartel members does not need to be seen. In this decision, there is only one piece of evidence and it is only in the form of a conclusion from an activity, even though in proving, one piece of evidence is not considered as evidence. Therefore it is necessary to further analyze the Use of Indirect Evidence in the Decision of the Commission for the Supervision of Business Competition Case Number 04 / KPPU-I / 2016 and Case Number 24 / KPPU-I / 2009 ".